Rapid crystallization of amorphous solid water by porosity induction. Issue 42 (24th October 2022) - Vishwakarma, Gaurav; Malla, Bijesh K.; Methikkalam, Rabin Rajan J.; Pradeep, Thalappil
Abstract : Rapid crystallization of amorphous solid water via acetonitrile diffusion–desorption induced porosity in the window of 128–134 K under ultrahigh vacuum. Abstract : Rapid crystallization of amorphous solid water (ASW) is often associated with crystallization that initiates at random nucleation sites in the bulk and expands in all directions. In this work, by preparing sandwich films of acetonitrile (ACN) and ASW in the form of ACN@ASW and ASW@ACN in an ultrahigh vacuum (UHV), we demonstrate a new method for rapid crystallization of ASW via ACN diffusion–desorption induced porosity in the ASW matrix even in the window of 128–134 K, well below the normal crystallization temperature of 155 K. By placing an HDO (5% D2 O in H2 O) probe layer in ASW, we found that when ACN diffuses and desorbs through ASW, it induces ASW crystallization where the crystal grows both from the top and from the bottom simultaneously into the bulk. Crystallization kinetics and activation energy ( E a ) for the formation of crystalline ice (CI) were evaluated using the Avrami equation and were compared with the previous reports. The evaluated E a was ∼53 kJ mol −1, close to the E a of crystal growth (47–56 kJ mol −1 ) and it suggested the absence of a nucleation process and supported rapid crystallization. Such occurrence of CI due to diffusion of ACN suggests a possible mechanism for the former's existence in many astrophysical environments.